Beyond structural injustice: Pursuing justice for workers in post‐pandemic global value chains. - Van Buren, Harry J.; Schrempf‐Stirling, Judith (Business Ethics, the Environment & Responsibility, 2022)
The COVID‐19 pandemic has exacerbated underlying and pre‐existing social, political, and economic conditions that make their negative effects both more likely and more negative, particularly for workers in global value chains (GVCs). In our conceptual and normative paper, we encourage a rethinking of GVCs and associated strategies of lead firms by integrating justice‐related concerns. We argue that the failure to provide just outcomes for GVC workers is due to the existence of persistent structural injustices within GVCs. We seek to address this fundamental question: if the problems of GVCs and employment are due to structural injustices, how can they be addressed and ameliorated? We offer operational principles for firms in this regard, using Iris Marion Young's concept of structural injustice to frame our analysis: (1) adopting shared constraint through inter‐firm cooperation and collective action, (2) minimum, shared standards for GVC worker treatment, (3) worker participation in GVC governance, (4) focusing on creating genuinely shared value rather than on value extraction from GVC workers, and (5) focusing on worker outcomes instead of processes. Our contribution lies in (1) outlining a relational approach to help lead firms to rethink their fundamental assumptions, strategies, and underlying conditions of GVCs and (2) expanding Young's analysis of structural injustice to GVCs more broadly.